2011
DOI: 10.1038/nrm3217
|View full text |Cite
|
Sign up to set email alerts
|

The N-end rule pathway: emerging functions and molecular principles of substrate recognition

Abstract: The N-end rule defines the protein-destabilizing activity of a given amino-terminal residue and its post-translational modification. Since its discovery 25 years ago, the pathway involved in the N-end rule has been thought to target only a limited set of specific substrates of the ubiquitin-proteasome system. Recent studies have provided insights into the components, substrates, functions and structural basis of substrate recognition. The N-end rule pathway is now emerging as a major cellular proteolytic syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
179
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(182 citation statements)
references
References 130 publications
0
179
1
2
Order By: Relevance
“…The N-end rule pathway uses the destabilizing amino-terminal residues of proteins as essential determinants (N-degrons) of their half-lives in vivo. 1,2 The N-degrons are the first defined degradation signals in eukaryotes and have later been identified even in bacteria, which lack Ub. 3,4 These findings suggest that N-degron-dependent proteolysis may be an evolutionary precursor of nature's selective degradation machinery through the "chambered proteases" in the cell.…”
Section: Introductionmentioning
confidence: 99%
“…The N-end rule pathway uses the destabilizing amino-terminal residues of proteins as essential determinants (N-degrons) of their half-lives in vivo. 1,2 The N-degrons are the first defined degradation signals in eukaryotes and have later been identified even in bacteria, which lack Ub. 3,4 These findings suggest that N-degron-dependent proteolysis may be an evolutionary precursor of nature's selective degradation machinery through the "chambered proteases" in the cell.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to type-1 and type-2 N-degrons, a recent study reported that acetylated N-terminal residues, occurring at 80% of human proteins, can function as N-degrons (13). The functions of the N-end rule pathway in degradation of short-lived proteins carrying N-degrons have been characterized in various processes (2,3). One outstanding question in the N-end rule pathway concerns differential functions of N-recognins that share binding specificity to N-terminal residues.…”
mentioning
confidence: 99%
“…N-degrons are generated within the cell when specific residues are exposed at the N terminus by proteolytic cleavage. There are two classes of destabilizing N-degrons: positively charged amino acids (Arg, Lys, and His) are of type 1, and bulky hydrophobic ones (Phe, Trp, Tyr, Leu, and Ile) are of type 2 [13].…”
Section: N-degronsmentioning
confidence: 99%
“…1a) (Fig 1b and 1c) [13,18,19]. In eukaryotes, the default N-terminal amino acid is Met (Nformylmethionine in bacteria).…”
Section: N-degronsmentioning
confidence: 99%